Business Strategy Development for Drilling Cutting’s Waste Industry using Ansoff Matrix: JEL Classification: M10, M21, L21, Q53, C44 - Rengga Atmaja Mauludin; Syarifa Hanoum (Journal La Bisecoman, 2025)
The drilling cutting’s waste industry in Indonesia still facing major challenges in handling the Volatile Organic Compound (VOC) content, requiring companies to adopt more robust business strategy. This research develop a business growth strategy for PT. GPS using integrated framework combining Business Model Canvas, SWOT-TOWS, Analytic Network Process (ANP) and Ansoff Matrix. The existing business model was analyzed to identify structural gaps, followed by SWOT-TOWS formulatioan and ANP weighting using expert judgements. The ANP result indicate the differentiation based strategies strengthening service quality and reliability (ST2) and improving customer retention (ST1) are to priorities. These strategies align with Product Development of Ansoff Matrix, while technology adoption (SO2) support Market Penetration.The new business model integrated these priorities into value prepositions, key activities, and revenue streams. Economic feasibility analysis showed positive NPV, IRR, BCR across three scenarios, confirmung the financial viability of the strategic directions. The integrated approach provides actionable strategic recommendations to enhance competitiveness and longterm sustainability.